The Communications And Multimedia Act 1998: Room For Estoppel? - Mohd. Hussein, Safinaz (Journal of Malaysian and Comparative Law, 1999)
In 1998, Malaysia passed the Communications and Multimedia Act 1998. This Act regulates the communications and multimedia industry which consists of three traditionally distinct industries of telecommunications, broadcasting and Information Technology (IT). Preceding the CMA 1998, two pieces of legislation governed the telecommunications and broadcasting industries. The Telecommunications Act 1950 governed the telecommunications industry and the Broadcasting Act 1988 governed the broadcasting industry. The IT industry which is now under the ambit of the CMA 1998 used to be, or prefers to refer to themselves as being highly 'unregulated'.